Growth and Biomass Performance of S7C20 Clone of Populus deltoides Marsh as Influenced by Plantation Period - Singh, Kundan; Rao, O. P.; Rana, B. S. (Indian Journal of Agroforestry, 2020)
Cuttings from clone S1C20 of Populus deltoides were planted at different time intervals in nursery beds to record the growth performance and biomass after one year's growth. The month of planting has significant impact on growth and biomass yield of cuttings. Cuttings planted in February had significantly (P=O.01) better growth and biomass performance, followed by planted in January while, cuttings planted in April exhibited poor growth and biomass production in all the plantation years i.e., 1997,1998 and 1999. On average stem, root and leaf components contributed 71.5, 23.1 and 5.4 %, respectively to total biomass production. Plant height had a significant (P=O.01) correlation with biomass, stem diameter and volume production after one year's growth. Biomass performance of seedling also exhibited significant (P=O.05) correlation with air/soil temperature and photoperiod (sunshine hour). However, there was no relationship between rainfall and growth performance of the clone planted at any time.